2015
DOI: 10.1111/rode.12154
|View full text |Cite
|
Sign up to set email alerts
|

Development Policy Implications for Growth and Regional Inequality in a Small Open Economy: The Indian Case

Abstract: Inclusive economic development has become a pressing goal of government policy in India in the face of rising regional inequality. This paper examines the role of targeted development policy action in inducing economic growth and also in reducing regional income inequality during the last two decades (since the beginning of the 1990s)-a period marked by increasing trade openness. In our disaggregated analysis of the states, we find that while the government capital expenditure policy has had significant positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Kim and colleagues found that income inequality in South Korea was positively correlated to the distribution of decentralization instruments, such as educational services, employment, infrastructure facilities, and information network access (2003). India's capital‐expenditure policy increases output by the poorer states, but fails to break the trend of rising regional inequality (Barua and Sawhney ). The once popular growth‐pole planning strategy stimulated very little development in lagging areas, and increased interregional development inequality, as evidenced by Pakistan (Siddiqi ).…”
Section: Sources and Factors Of Spatial Inequality In Asiamentioning
confidence: 99%
“…Kim and colleagues found that income inequality in South Korea was positively correlated to the distribution of decentralization instruments, such as educational services, employment, infrastructure facilities, and information network access (2003). India's capital‐expenditure policy increases output by the poorer states, but fails to break the trend of rising regional inequality (Barua and Sawhney ). The once popular growth‐pole planning strategy stimulated very little development in lagging areas, and increased interregional development inequality, as evidenced by Pakistan (Siddiqi ).…”
Section: Sources and Factors Of Spatial Inequality In Asiamentioning
confidence: 99%
“…This improves the production efficiency by shifting the activities to countries that have a comparative advantage in specialising or producing them. Hence, the regions that have a higher degree of openness are expected to have higher economic growth (Barua and Sawhney, 2015;Jiang, 2014;Maiti and Marjit, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The studies IGDR 14,2 on the linkage between trade and growth at the sub-national level in India are very few due to the unavailability of data. The existing studies have used various proxies of international trade as in Maiti and Marjit (2015) and Barua and Sawhney (2015). However, generating the comparable data on exports and imports between the states in India and provinces in the PRC is a daunting task for an individual researcher.…”
Section: Introductionmentioning
confidence: 99%
“…1 Among large emerging economies, in 2011 the Gini coefficient stood at 0.634, 0.542, 0.531, 0.481, 0.474, and 0.41 for South Africa, Columbia, Brazil, Mexico, China, and Russia, respectively. 2 These high levels of income inequality and the widespread increase in such inequality in recent decades has spurred active public policy discourse over the impact of rising inequality on economic development.…”
Section: Introductionmentioning
confidence: 99%